1999
DOI: 10.1002/(sici)1522-726x(199908)47:4<415::aid-ccd8>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stent thrombosis after primary stenting for acute myocardial infarction

Abstract: The aim of the study was to determine if a hypercoagulable state that may persist for several months after an acute myocardial infarction may contribute to an increased incidence of stent thrombosis. Primary stenting was performed in 104 consecutive patients with acute myocardial infarction using 147 coronary stents. Twenty‐eight patients (27%) were diabetic and 55 patients (53%) were smokers. A single stent was placed in 63%, two stents in 33%, and more than two stents in 4% of the patients. Procedural succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…5 Â ULN) in 37 (39%) cases. Although the size of myocardial infarction in our study compares favourably with previous reports 29 of infarct size in patients with stent thrombosis, myocardial infarction related to stent thrombosis was associated with a significant decline in left ventricular function. This finding raises concern as left ventricular function has been identified as a strong and consistent predictor of long-term survival following myocardial infarction.…”
Section: Procedural Outcome Of Emergency Pci For Treatment Of Stent Thrombosissupporting
confidence: 72%
“…5 Â ULN) in 37 (39%) cases. Although the size of myocardial infarction in our study compares favourably with previous reports 29 of infarct size in patients with stent thrombosis, myocardial infarction related to stent thrombosis was associated with a significant decline in left ventricular function. This finding raises concern as left ventricular function has been identified as a strong and consistent predictor of long-term survival following myocardial infarction.…”
Section: Procedural Outcome Of Emergency Pci For Treatment Of Stent Thrombosissupporting
confidence: 72%
“…Soon, drug-eluting stents have resulted in decreased restenosis rates in treatment of de novo coronary stenosis [8,9]. Diabetes mellitus and smoking were demonstrated as predictors of stent thrombosis [10]. In our study, four out of six diabetic patients had occluded stents, also there were six smokers and they all had occluded stents.…”
Section: Resultssupporting
confidence: 48%
“…In a cohort of 104 consecutive patients undergoing primary stenting for STEMI, Silva et al demonstrated that the only independent predictors of stent thrombosis were diabetes and tobacco use. 30 This finding may reflect the heightened platelet activation and aggregation among patients with diabetes suffering from an acute STEMI.…”
Section: Primary Percutaneous Coronary Intervention (Pci)mentioning
confidence: 99%